Antibiotic resistant enterococci in laboratory reared stored-product insect species and their diets - Byington, Sarah (Kansas State University, 2016)
Stored-product insects and stored products from feed mills and swine farms contain antibiotic and potentially virulent Enterococcus faecalis, Enterococcus faecium, Enterococcus casseliflavus, Enterococcus gallinarum, and Enterococcus hirae. Stored-product insects can serve as potential vectors of these enterococci which possess antibiotic resistance genes that can be spread by horizontal transfer to more serious human pathogens. In the present study, the species and concentration of enterococci from adults and larvae of key stored-product insects and insect diets and their antibiotic resistance profile were characterized. Adults of five species out of the 15 stored-product insects were tested positive for enterococci, and these included Callosobruchus maculatus (F.), Sitophilus granarius (L.), Stegobium paniceum (L.), Lasioderma serricorne (F.), and Sitophilus zeamais Motschulsky. Three enterococcal species (E. casseliflavus, E. faecalis, and E. faecium) were found in 53 to 97% of the 30 adults screened for each insect species, and the enterococcal concentrations ranged from 1.4 x 10³ to 3.1 x 10⁶ CFU/adult. About 10 to 100% of the mature larvae of the respective five insect species had these three enterococcal species with concentrations ranging from 0.3 x 10¹ to 1.4 x 10⁵ CFU/larvae. Only three of the eight insect diets screened had the same three enterococci species in addition to E. gallinarum and E. hirae at concentrations of 0.2 x 10¹ to 5.9 x 10³ CFU/g. The greatest enterococcal concentration was found in C. maculatus adults but not in their larvae or diet (cowpeas). In C. maculatus during a nine-day period after adult eclosion, the enterococcal concentrations increased exponentially from 0.6 x 10¹ to a maximum of 4.1 x 10⁷ CFU/adult. Enterococci were detected in the fecal material of C. maculatus during a four-day period with a maximum concentration of 3.3 x 10³ CFU/adult on the fourth day. A total of 298 enterococcal isolates from adults, larvae, and diets were represented by E. faecalis (51.7% of the total), E. faecium (19.1%), E. casseliflavus (18.8%), E. gallinarum (5.7%), and E. hirae (4.7%). Enterococci were phenotypically resistant to quinupristin (51.3% of the total), erythromycin (38.9%), tetracycline (30.1%), enrofloxacin (29.2%), doxycycline (11.5%), and tigecycline (2.7%). All isolates were susceptible to ampicillin and vancomycin.
Keywords: Laboratory cultures; Insect diets; Enterococci; Antibiotic resistanceStored product insects